2010
DOI: 10.1093/molbev/msq059
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Evidence for Separate Acquisition of Plastids in Cryptophytes, Haptophytes, and Stramenopiles

Abstract: According to the chromalveolate hypothesis (Cavalier-Smith T. 1999. Principles of protein and lipid targeting in secondary symbiogenesis: euglenoid, dinoflagellate, and sporozoan plastid origins and the eukaryote family tree. J Eukaryot Microbiol 46:347-366), the four eukaryotic groups with chlorophyll c-containing plastids originate from a single photosynthetic ancestor, which acquired its plastids by secondary endosymbiosis with a red alga. So far, molecular phylogenies have failed to either support or dispr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(208 citation statements)
references
References 57 publications
14
193
1
Order By: Relevance
“…We investigated the placement of the Archaeplastida lineage within the cyanobacterial phylum by building a "plastidome tree" using a concatenation of 25 conserved plastid proteins. Although most studies support the monophyly of primary plastids (16,17), others have reported a polyphyletic origin (18,19). We find strong support for the monophyletic placement of plastids near the base of the cyanobacterial tree ( Fig.…”
Section: Prochlorococcus Marinus Mit 9215supporting
confidence: 59%
“…We investigated the placement of the Archaeplastida lineage within the cyanobacterial phylum by building a "plastidome tree" using a concatenation of 25 conserved plastid proteins. Although most studies support the monophyly of primary plastids (16,17), others have reported a polyphyletic origin (18,19). We find strong support for the monophyletic placement of plastids near the base of the cyanobacterial tree ( Fig.…”
Section: Prochlorococcus Marinus Mit 9215supporting
confidence: 59%
“…Together with diatoms, brown algae, and golden-brown algae, oomycetes are classified as stramenopiles, a lineage that is united with alveolates in the supergroup of chromalveolates (Baldauf et al, 2000;Yoon et al, 2002). The monophyly of this supergroup, however, is under debate (Baurain et al, 2010). The genomes of oomycetes sequenced so far are variable in size and content, ranging from 65 Mb in Phytophthora ramorum to 240 Mb in P. infestans (Haas et al, 2009), and only include plant pathogenic species.…”
mentioning
confidence: 99%
“…These plastids also differ from primary plastids in that they contain chlorophylls a+c, or chlorophylls a+b (euglenids, chlorarachniophytes) instead of only chlorophyll a. The chlorophyll a+c lineages are often collectively referred to as the chromalveolates (Cavalier-Smith, 1999) although this group has recently been shown to be paraphyletic in the tree of life (Hackett et al, 2007;Baurain et al, 2010). The additional membrane layers in complex plastids have been attributed to additional endosymbiosis event(s) involving an already plastid-bearing, eukaryote endosymbiont, instead of a cyanobacterium.…”
Section: Secondary (And Tertiary) Plastidsmentioning
confidence: 99%
“…See also: Alveolates; Chromista Phylogenetic analysis of plastid-encoded genes in most chromalveolates shows a red algal origin of the organelle (Khan and Archibald, 2008) (see Figure 1a); regardless of whether it originated via a single red algal endosymbiosis as suggested by Cavalier-Smith or potentially by serial endosymbioses in different lineages, that is, one chromalveolate engulfs another, followed by plastid replacement. Such an alternative to the chromalveolate hypothesis is the independent acquisition hypothesis (also known as serial eukaryote-eukaryote endosymbiosis, or the serial EEE; Baurain et al, 2010), which suggests that the origin of the secondary plastids in different groups of chromalveolates, for example, haptophytes, cryptophytes and stramenopiles, is the result of independent, serial endosymbioses involving unicellular eukaryotes, not necessarily red algae. Under this scenario, the invocation of massive gene loss events or the subsequent loss of the red algal endosymbiont is unnecessary to explain the nonplastid containing lineages of chromalveolates such as ciliates.…”
Section: Secondary (And Tertiary) Plastidsmentioning
confidence: 99%